Integration of Indonesian National Trauma Guideline into the Emergency Room System (Cipto Code Trauma System) - Radi Muharris Mulyana; Ascobat Gani (Journal of Epidemiology and Public Health, 2025)
Background: Indonesia has enacted the national trauma guideline since 2017 and Cipto Mangun-kusumo Hospital (CMH) has applied it since 2019 through the establishment of Cipto Code Trauma. This study aimed to describe the compliance, system adherence, performance and outcome associated with the Cipto Code Trauma system.Subjects and Method: This cross-sectional study was conducted at CMH Emergency Room (ER) using direct observations and data from electronic health records (EHRs). Observations were performed on 106 trauma cases by convenience sampling to map clinical and non-clinical components using a checklist. We compared the implemented ER components against the 2017 national trauma guidelines, assessing the system compliance. Total sampling from EHRs was performed on 4,317 trauma patients to assess performance and outcome of Cipto Code Trauma system. The data were analyzed descriptively.Results: Observations from 106 trauma cases indicate that the Cipto Code Trauma meets all criteria from the national trauma guidelines. Performance indicators from 840 patients were achieved, including trauma team activation (87.6%), on-site multidisciplinary consultation (87.6%), time to physician assessment within five minutes (84.4%), except for length of stay under 4 hours (18.5%) and time to operating theatre within two hours (45.5%). Among the 4,317 trauma cases, the mortality rate for patients in the resuscitation category was 0.4%, while 39% of these patients were discharged directly from the ER.Conclusion: The Cipto Code Trauma at CMH has successfully integrated the Indonesian national trauma guidelines, meeting all required standards. However, further improvements are needed to enhance system adherence and performance.